GEOGRAPHICAL INFORMATION SYSTEMS AND THEIR APPLICATION IN VARIOUS FIELDS: GEOGRAPHICAL INFORMATION SYSTEMS AND THEIR APPLICATION IN VARIOUS FIELDS - Dimanova, Donika (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
Geographic information systems are powerful tools for collecting, analyzing and visualizing geographic data to support decision making in a variety of activities. The aim of this paper is to present the basic principles of GIS and their applications in various fields ranging from ecology and urban planning to health and security. GIS plays an important role in the modern world, enabling better understanding and management of spatial processes and phenomena.